INTERNALISASI NILAI-NILAI PENDIDIKAN KARAKTER DALAM KELUARGA SEBAGAI BASIS PEMBENTUKAN KEPRIBADIAN ANAK - Sri Wahyuni; Annisa; Indriayu Ramadhani; Miftha Hulladuni Riandi; Putri Ramadhon (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Character education is an essential aspect in shaping children's personality, especially in the era of globalization and digitalization which brings various moral challenges. This study aims to describe the process of internalizing character education values within the family and to analyze the role of the family as the primary basis for children's personality development. This research employs a qualitative approach with a library research method, utilizing relevant scientific literature as data sources. Data were collected through documentation techniques and analyzed using content analysis. The findings indicate that the internalization of character values in the family is carried out through role modeling, habituation, effective communication, and consistent supervision. The family plays a strategic role as the first environment in shaping children's character, although it faces various challenges such as technological influence, parents' busyness, and social environment. Therefore, strong commitment and appropriate strategies from parents, along with collaboration with educational institutions, are necessary to optimize children's personality development.